Rendemen Minyak dan Gel Biodiesel dari Ekstrak Biji Palem Putri (Adonidia Merrillii) dengan Metode Soxhlet - Mahfudhillah, Hamim; Nabihah, Arinza Aulydiana; Choirudin, Hana Haifa; Khuriyah, Siti Imroatul (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2024)
Biodiesel consists of various long-chain methyl ester fatty acids which can be produced from renewable sources, for example, oil from palm seed extract (Adonidia merrillii). This research aims to determine the yield of extracted oil and biodiesel from putri palm seed oil. This research is experimental research with a quantitative descriptive approach. The extraction process was carried out using a Soxhlet apparatus with n-hexane solvent. The extracted oil is then tested for its characteristics, esterified and transesterified to produce biodiesel. Based on the research conducted, it was found that the oil yield from extraction was 0.47% or quite low. However, the biodiesel yield from putri palm seed oil is quite high, namely 87.66%. This research produces biodiesel in gel form at room temperature. This biodiesel gel is the first and newest discovery in the field of renewable energy sources. Biodiesel gel can be used as fuel for portable cooking equipment and food heaters to keep buffet and catering dishes warm.